2012
DOI: 10.1007/s00299-012-1245-9
|View full text |Cite
|
Sign up to set email alerts
|

Reference gene selection for qPCR in Ammopiptanthus mongolicus under abiotic stresses and expression analysis of seven ROS-scavenging enzyme genes

Abstract: Ammopiptanthus mongolicus, the only evergreen broadleaf shrub endemic to the northwest desert of China, is a valuable species for plant abiotic stress research. No report has so far described the selection of reference genes to get stringent normalization for qPCR in A. mongolicus. This work identified reliable reference genes for normalization of qPCR data in A. mongolicus under abiotic stresses from 14 reference gene candidates (UBQ, Tub1, Tub2, Abc1, Ubc1, Ubc2, Ubc4, Ubc5, eIF1, eIF2, eIF3, eIF4, EF1, EF2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
(37 reference statements)
1
22
0
Order By: Relevance
“…In the present study, TIP41 was the most unstable in groups involving different tissues. Among the members of the ubiquitin-conjugating enzyme gene family, it was reported in Ammopiptanthus mongolicus that UBC5 and UBC1 represent the best combination for normalization of differentially expressed genes under cold stress, UBC2 under salt stress, and UBC4 and UBC5 under heat stress (Shi et al 2012). In this study, UBC8 showed the most stable expression in groups of different cultivars and UBC21 was the most suitable gene in samples exposed to different temperatures, as analyzed by geNorm.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, TIP41 was the most unstable in groups involving different tissues. Among the members of the ubiquitin-conjugating enzyme gene family, it was reported in Ammopiptanthus mongolicus that UBC5 and UBC1 represent the best combination for normalization of differentially expressed genes under cold stress, UBC2 under salt stress, and UBC4 and UBC5 under heat stress (Shi et al 2012). In this study, UBC8 showed the most stable expression in groups of different cultivars and UBC21 was the most suitable gene in samples exposed to different temperatures, as analyzed by geNorm.…”
Section: Discussionmentioning
confidence: 94%
“…To evaluate the expression profiles of PbCBL7 gene under various experimental conditions, its relative transcript levels were normalized by the geometric average of the three most reliable reference genes selected in all the sample pools in this study through the equation of relative ratio target gene/control = ðE ÀC t Target gene Target gene Pfaffl 2001;Shi et al 2012). Calculations were carried out with Microsoft Excel software.…”
Section: Expression Of Pbcbl7 Gene Under Different Abiotic Stressesmentioning
confidence: 99%
“…Real-time PCR was carried out as duplicates and control samples without template or with RNA alone without reverse transcription were included as checks for potential contamination with genomic DNA. Twenty (20) µl of each reaction were run on 2% agarose gels stained with ethidium bromide to check the specificity of amplification. The DNA fragments were recovered using the QIAquick gel extraction kit (QIAGEN Inc., Mississauga, ON, Canada) and confirmed by sequencing.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Furthermore, the treatments (salt stress or drought stress) are simple and similar among various studies. Hence, we made an integrated analysis in terms of the stability of RGs under the two conditions from various studies.The 26 works of that designedly evaluated suitable RGs under salt stress within 24 plant species were collected(Bin et al 2012;Borges et al 2012;Castro et al 2012;Chandna et al 2012;Chang et al 2012;Chi et al 2012;Cordoba et al 2011;de Carvalho et al 2013;Dombrowski and Martin 2009;Dong et al 2012;Gao et al 2012;Garg et al 2010;Hong et al 2008;Kumar et al 2013;Kundu et al 2013;Le et al 2012;Lee et al 2010a;Nicot et al 2005;Obrero et al 2011;Park et al 2012;Reddy et al 2013;Schmidt and Delaney 2010;Shi et al 2012;Wan et al 2010;Wei et al 2013;Zhu et al 2013). As shown inTable S1, plants were subjected to salt stress by treating with NaCl solution, although the NaCl concentration and stress time differ in various studies.…”
mentioning
confidence: 99%
“…Statistic analysis of reference gene stability under drought stressFor the analysis of reference genes under drought stress, 27 publications within 26 plant species were collected in Table S2(Bin et al 2012;Borges et al 2012;Carvalho et al 2010;Chandna et al 2012;Chang et al 2012;Cruz et al 2009;Dombrowski and Martin 2009;Dong et al 2012;Garg et al 2010;Goulao et al 2012;Hong et al 2008;Janska et al 2013;Kumar et al 2013;Kundu et al 2013;Le et al 2012; Lee et al 2010a, b;Maksup et al 2013;Park et al 2012;Qi et al 2010;Reddy et al 2013;Schmidt and Delaney 2010;Shi et al 2012;Wan et al 2010;Wei et al 2013;Zhang et al 2013;Zhu et al 2013).…”
mentioning
confidence: 99%